PENGARUH KAS, DANA PIHAK KETIGA, SERTIFIKAT WADIAH BANK INDONESIA, PROFIT MARGIN, DAN NON-PERFORMING FINANCING TERHADAP PEMBIAYAAN MURABAHAH (STUDI EMPIRIS PADA BANK SYARIAH PERIODE TAHUN 2006-2008) - Lina Nurhasanah; Emile Satia Darma (Journal of Accounting and Investment, 2009)
The purpose of this research is to find out the relationship between cash, third party fund, SWBI (Sertifikat Waddiah Bank Indonesia) ond NPF (Non Performung Financing) to murabahah financing in ths ayontah bank in Indonesia period 2006-2008. For all trials in this research, trial of quality of data and also hypothesis trial use SPSS program. In this research, classic assumption test is used to examine data quality, whereas for testing the hypothesis, this research use t-test analysis method. Research result showed that all of classic assumption test can be accomplished in this research. Stimulants trials showed that all Independent (cash, third party fund, SWBI (Sertifikat Wadiah Bank Indonesia), profit margin, and NPF (Non Performing Financing) had an effect on murabahah financing. patrial test (t-test) showed that the third party fund had a positive effect to murabahah financing, SWBI had a negative affect to murabahah financing. Whereas, another independent variables (cash and profit margin) did not have a positive effect to murabahah financing. And the last. NPF did not hava a negative affect to murabahah financing.